Experiences Of Persons With Lower Limb Prosthesis In A Selected Orthopedic Center In Eastern Region Of Ghana - Dordunu, R. (University of Ghana, 2021)
Persons with lower limb amputation (LLA) experience a myriad of physical, psychological and functional problems. Although, ambulation with a prosthesis is the goal of rehabilitation for persons with LLA, there is limited empirical data on the usability, adaptability and the comfort associated with prosthesis usage amongst users. This study therefore sought to explore experiences of persons with lower limb prosthesis in the Eastern region of Ghana using the Social-Ecological model. Exploratory descriptive qualitative design was used for the study. Overall, seventeen (17) participants were purposefully recruited for the study. Data was collected using a semi-structured interview guide. The interview was audio-taped, transcribed verbatim and analyzed deductively using thematic content analysis. The findings show that prosthetic users experience internal stigma, physical discomforts from the prosthesis, difficulty adjusting to sex-life and depended upon their family and friends for support. Additional finding shows that, prosthetic users experience discrimination and challenges with participating in community activities. Also, participants experience challenges with accessing healthcare facilities and high cost in securing or repairing a prosthetic foot. However, participants utilized social media, listening to music, reading the Bible or Quran to cope with the challenges. Interventions for addressing stigma, discrimination and cost of prosthesis are required to improve the lived experiences of persons with lower limb prosthesis.
MPhil. Nursing
Keywords: Eastern Region Of Ghana; Lower Limb Prosthesis; Orthopedic